1999
DOI: 10.1038/22336
|View full text |Cite
|
Sign up to set email alerts
|

The cell-surface proteoglycan Dally regulates Wingless signalling in Drosophila

Abstract: Wingless (Wg) is a member of the Wnt family of growth factors, secreted proteins that control proliferation and differentiation during development. Studies in Drosophila have shown that responses to Wg require cell-surface heparan sulphate, a glycosaminoglycan component of proteoglycans. These findings suggest that a cell-surface proteoglycan is a component of a Wg/Wnt receptor complex. We demonstrate here that the protein encoded by the division abnormally delayed (dally) gene is a cell-surface, heparan-sulph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
237
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(253 citation statements)
references
References 28 publications
(11 reference statements)
10
237
2
1
Order By: Relevance
“…The specific functions of glypicans are still not well understood, but their localization on the cell surface and experimental data indicate that glypicans are involved in the regulation of interactions between growth factors and their receptors (overviews in David, 1993;Bernfield et al, 1999;Perrimon and Bernfield, 2000). For example, human glypican-1 (GPC1) can stimulate 'heparin-binding' growth factors such as basic fibroblast growth factor (FGF) and growth factor receptor interactions and signalling (Steinfeld et al, 1996); or dally, the Drosophila melanogaster homologue to human glypicans, controls cellular responses to decapentaplegic, a TGF (transforming growth factor) b-related morphogen (Jackson et al, 1997), and can influence signalling mediated by wingless, a member of the Wnt family of growth factors, secreted proteins that control proliferation and differentiation during development (Tsuda et al, 1999). It has been proposed that GPC3 negatively regulates insulinlike growth factor-II (IGF-II) activity by competing for IGF-II binding with the signalling receptor for IGF-II, IGF-I receptor .…”
Section: Discussionmentioning
confidence: 99%
“…The specific functions of glypicans are still not well understood, but their localization on the cell surface and experimental data indicate that glypicans are involved in the regulation of interactions between growth factors and their receptors (overviews in David, 1993;Bernfield et al, 1999;Perrimon and Bernfield, 2000). For example, human glypican-1 (GPC1) can stimulate 'heparin-binding' growth factors such as basic fibroblast growth factor (FGF) and growth factor receptor interactions and signalling (Steinfeld et al, 1996); or dally, the Drosophila melanogaster homologue to human glypicans, controls cellular responses to decapentaplegic, a TGF (transforming growth factor) b-related morphogen (Jackson et al, 1997), and can influence signalling mediated by wingless, a member of the Wnt family of growth factors, secreted proteins that control proliferation and differentiation during development (Tsuda et al, 1999). It has been proposed that GPC3 negatively regulates insulinlike growth factor-II (IGF-II) activity by competing for IGF-II binding with the signalling receptor for IGF-II, IGF-I receptor .…”
Section: Discussionmentioning
confidence: 99%
“…Given that glypicans have been shown to regulate both canonical or non-canonical signaling (21,22,47), and given that non-canonical Wnt signaling can inhibit canonical signaling (48 -54), it is possible that the increase in canonical Wnt signaling observed in the GPC3-null embryos could be the result of either the direct stimulation of the canonical Wnt pathway or an indirect consequence of the inhibition of a non-canonical Wnt pathway. We therefore decided to investigate whether there are alterations in non-canonical Wnt signaling in the mice lacking GPC3.…”
Section: Gpc3 Knockout Mice Exhibit Alterations In Wntmentioning
confidence: 99%
“…Recent studies on Drosophila demonstrated that the mutation of some genes required for proteoglycan biosynthesis, dally (27,28), sugarless (29 -32), and tout-velu (32,33), resulted in defective signaling during development. A number of reports have suggested that heparan sulfate proteoglycans are involved in a variety of signaling pathways, in particular those of fibroblast growth factor (34), Wnt/Wingless (35), Decapentaplegic (27), and Hedgehog (36). Heparan sulfate proteoglycans are thought to be required for stabilizing the complex between a ligand and its receptors or restricting the extracellular diffusion of ligands (35).…”
Section: Fig 2 Subcellular Localization Of Papst1 Proteinmentioning
confidence: 99%